Incidental solid renal mass in a cadaveric donor kidney - Meyyappan, R. M. (Medknow Publications & Media Pvt Ltd, 2012)
The number of patients living with end-stage renal disease (ESRD) is increasing in our country and demand for renal grafts is ever increasing. Cadaver renal transplantation is being established as a viable supplement to live transplantation. We present a case where a mass lesion was encountered in the donor kidney from a cadaver. Enucleation of the lesion was done and we proceeded with the grafting. Histopathological examination showed a ‘Renomedullary interstitial cell tumour’, a rare benign lesion. Post transplant, the renal function recovered well and the patient is asymptomatic. Such incidental renal masses present an ethical dilemma to the operating surgeon.